LIVER TRANSPLANTATION: DONOR SOURCES, TYPES OF TRANSPLANTS AND PIGGYBACK TECHNIQUES (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
Liver transplantation is one of the most effective treatment methods for end-stage liver diseases. This thesis highlights donor sources, types of liver grafts, indications for transplantation, and surgical techniques for managing the inferior vena cava using Piggyback approaches.